2021
DOI: 10.1002/kjm2.12363
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA UCA1 negatively regulates NF‐kB activity in psoriatic keratinocytes through the miR125a‐A20 axis

Abstract: Psoriasis is one of the most common chronic inflammatory skin diseases that affects approximately 3% of the world's population. Hyper proliferation, infiltration of inflammatory cells and aberrant differentiation of keratinocytes are the three most important characteristics of psoriasis. Previous reports showed that NF‐κBis the crucial mediator linking psoriatic keratinocytes and immune cell states through its effects on chemokine and cytokine production. To identify the role of NF‐κB in psoriasis, we conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
10
1
Order By: Relevance
“…When evaluating gene expression patterns in lesional compared to control skin, DANCR was upregulated and TINCR was downregulated in psoriasis lesional skin ( Figure 1A ). These findings support our current understanding of psoriasis as an inflammatory skin disease that is in part characterized by poor differentiation of keratinocytes ( Ma et al, 2021 ). Of importance, we discovered that TINCR was also downregulated in atopic dermatitis lesional skin—a finding that has not previously been reported.…”
Section: Reviewsupporting
confidence: 86%
See 4 more Smart Citations
“…When evaluating gene expression patterns in lesional compared to control skin, DANCR was upregulated and TINCR was downregulated in psoriasis lesional skin ( Figure 1A ). These findings support our current understanding of psoriasis as an inflammatory skin disease that is in part characterized by poor differentiation of keratinocytes ( Ma et al, 2021 ). Of importance, we discovered that TINCR was also downregulated in atopic dermatitis lesional skin—a finding that has not previously been reported.…”
Section: Reviewsupporting
confidence: 86%
“…It is also involved in cellular stress response and may play a role in psoriasis by decreasing sensitivity to keratinocyte apoptosis via the regulation of G1P3 ( Sonkoly et al, 2005 ; Zenz et al, 2005 ; Bari et al, 2011 ; Szegedi et al, 2012 ). Ma et al demonstrated that lncRNA UCA1 (urothelial carcinoma-associated 1) was downregulated in psoriatic lesional skin ( Ma et al, 2021 ). Initially named for its high expression in bladder cancer cells ( Roberson and Bowcock, 2010 ; Ma et al, 2021 ), UCA1 has now gained more attention regarding its role in psoriasis ( Ma et al, 2021 ).…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations